T cell phenotype switching in autoimmune disorders: Clinical significance of targeting metabolism. Issue 7 (29th July 2022) - Barberis, Matteo; Rojas López, Alejandra
Abstract: Increasing efforts points to the understanding of how to maximize the capabilities of the adaptive immune system to fight against the development of immune and inflammatory disorders. Here we focus on the role of T cells as immune cells which subtype imbalance may lead to disease onset. Specifically, we propose that autoimmune disorders may develop as a consequence of a metabolic imbalance that modulates switching between T cell phenotypes. We highlight a Systems Biology strategy that integrates computational metabolic modelling with experimental data to investigate the metabolic requirements of T cell phenotypes, and to predict metabolic genes that may be targeted in autoimmune inflammatory diseases. Thus, we propose a new perspective of targeting T cell metabolism to modulate the immune response and prevent T cell phenotype imbalance, which may help to repurpose already existing drugs targeting metabolism for therapeutic treatment. Abstract : An imbalance in T cell phenotype switching triggers autoimmune disorders. The imbalance may initiate during the regulation of any of the interconnected cellular components that modulate T cell biology: environmental cues, signaling pathways, cytokine‐mediated regulation, cell‐to‐cell communication, cell cycle, metabolism, and microbiome. Failure of the coordination among these responses may kickstart the process of anomalous Th cell behavior, with the resulting Th cell phenotype imbalance potentially resulting in a switch from a healthy state to a disease state, thereby in the onset of autoimmune/autoinflammatory disorders.